2016
DOI: 10.1111/jgs.13937
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Small Decrease in Serum Sodium Concentration within the Normal Range and All‐Cause and Cardiovascular Mortality in Elderly Adults over 5 Years

Abstract: A slightly lower serum sodium concentration within the normal range was a major risk factor for mortality in elderly adults. Sodium level corrected according to serum glucose concentration was a more meaningful risk factor than measured sodium level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Because of the diluting effect of hyperglycemia on sodium concentration, the true value of s-sodium in hyperglycemic patients is glucose-corrected sodium [28]. One previous study demonstrated the superiority of glucose-corrected serum-sodium to predict mortality over measured serum-sodium, and the authors suggested that glucose-corrected serum-sodium should be considered in studies analyzing serum-sodium [31]. To our knowledge our study is the first study to report serum-sodium and glucose-corrected serum-sodium in an unselected hospital population.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the diluting effect of hyperglycemia on sodium concentration, the true value of s-sodium in hyperglycemic patients is glucose-corrected sodium [28]. One previous study demonstrated the superiority of glucose-corrected serum-sodium to predict mortality over measured serum-sodium, and the authors suggested that glucose-corrected serum-sodium should be considered in studies analyzing serum-sodium [31]. To our knowledge our study is the first study to report serum-sodium and glucose-corrected serum-sodium in an unselected hospital population.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium is widely accepted as a risk factor that increases blood pressure 11,42 . However, in recent studies, serum sodium was also found to be inversely associated with cardiovascular risk and mortality 12–14 . Sodium may have pleiotropic effects on the cardiovascular system and glucose metabolism 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Dietary sodium is associated with serum sodium, 10 and serum sodium is also known as a factor that could increase the risk of hypertension 11 . However, some studies found that lower serum sodium, even within the normal range, is associated with poor prognosis 12–14 . Meanwhile, hyponatremia is independently associated with an increased risk of diabetes 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 One previous study demonstrated the superiority of glucose-corrected serum-sodium to predict mortality over measured serum-sodium, and the authors suggested that glucose-corrected serum-sodium should be considered in studies analyzing serum-sodium. 16 It is well known that dysnatremia is associated with longer hospital stay. According to a recent meta-analysis by Corona et al, investigating 46 studies, mean hospital stay was 3 days longer in hyponatremic patients.…”
Section: Discussionmentioning
confidence: 99%